2013
DOI: 10.1017/s1751731113000852
|View full text |Cite
|
Sign up to set email alerts
|

Plant components with specific activities against rumen methanogens

Abstract: A wide range of plant bioactive components (phytochemicals) have been identified as having potential to modulate the processes of fermentation in the rumen. The use of plants or plant extracts as natural feed additives has become a subject of interest not only among nutritionists but also other scientists. Although a large number of phytochemicals (e.g. saponins, tannins and essential oils) have recently been investigated for their methane reduction potential, there have not yet been major breakthroughs that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 107 publications
7
102
0
8
Order By: Relevance
“…Guo et al (2008) demonstrated that saponins inhibited the expression of the methylcoenzyme M reductase (mcrA) gene which takes part in the final step of methanogenesis. In addition, the CH 4 -suppressing effects of saponins were presumably a direct action against the rumen microbes involved in CH 4 formation, including methanogens and protozoa (Cieslak et al, 2013(Cieslak et al, , 2016Anantasook et al, 2016). Similar findings were found in this study: the protozoal population was also linearly reduced with increased DR seed meal levels Table 3.…”
Section: −1supporting
confidence: 84%
See 1 more Smart Citation
“…Guo et al (2008) demonstrated that saponins inhibited the expression of the methylcoenzyme M reductase (mcrA) gene which takes part in the final step of methanogenesis. In addition, the CH 4 -suppressing effects of saponins were presumably a direct action against the rumen microbes involved in CH 4 formation, including methanogens and protozoa (Cieslak et al, 2013(Cieslak et al, , 2016Anantasook et al, 2016). Similar findings were found in this study: the protozoal population was also linearly reduced with increased DR seed meal levels Table 3.…”
Section: −1supporting
confidence: 84%
“…Plant secondary compounds have been reported to suppress CH 4 concentration, reduce rumen protozoa counts and modulate rumen fermentation patterns (Cieslak et al, 2013). Many studies have shown that forages containing condensed tannins reduce CH 4 emissions from ruminants (Guo et al, 2008;Cieslak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Isso pode ser explicado pelo maior conteúdo de proteína desse alimento, como mostra a Tab. 1, o que resultaria na formação de bicarbonato de amônio, a partir de CO 2 , reduzindo a sua contribuição para a produção de gás (Cieslak et al, 2013). Além disso, as sementes da moringa têm demonstrado efeito bactericida contra algumas cepas Grampositivas e Gram-negativas, sugerindo o uso das sementes como fontes de agentes antibacterianos (Costa et al, 2009).…”
Section: Discussionunclassified
“…Em relação aos demais, demonstra melhor disponibilidade de nutrientes para os microrganismos ruminais in vitro. Esse tempo é considerado limite para a permanência de grãos no rúmen para vacas em lactação com taxa de passagem de 4 a 6,5% h -1 e, dessa maneira, promoveria maior disponibilidade de energia fermentável no rúmen agindo em sincronia com a proteína degradável (Cieslak et al, 2013), o que resultaria em maiores produções de leite.…”
Section: Discussionunclassified
“…fat and fatty acids) and proteins may naturally restrict the production of CH 4 in the rumen if their relative proportion is increased and daily DMI is kept the same. Literature review of experimental research (Tedeschi et al, 2003 and2011b;Cieslak et al, 2013) has indicated that in current production systems such mitigation might be attained with feed additives and feeding strategies used alone or combined. Regardless of limitations in measuring CT and the generally unknown fate and transformations of the CT molecule through the ruminant digestive system (Terrill et al, 1994), CT are thought to reduce CH 4 production in two ways.…”
Section: Potential Benefits Of Ctmentioning
confidence: 99%